Bridging Neurobiology and Behavior: A Mixed-Methods Study of Scientific Literacy in Psychiatric Contexts Among Biology Education Students' - Wahyuni, Wahyuni; Anto, Ambo; Faisal, Faisal; Susiati, Asih Luklu (Biology Teaching and Learning, 2025)
Abstract. This study aims to analyze biology education students’ scientific literacy in psychiatric contexts, particularly in interpreting neurobiological mechanisms and behavior. A mixed-methods approach with a convergent parallel design was employed, involving 40 students. Data were collected through scenario-based tests (stress, anxiety, depression) and in-depth interviews. Quantitative data were analyzed using descriptive statistics and One-Way ANOVA, while qualitative data were examined through thematic analysis. The results indicate that scientific literacy is at a moderate level, with higher performance in explaining biological phenomena than in interpreting behavior and making evidence-based decisions. Significant differences were found across cases (p < 0.01), with the lowest performance in depression cases. Qualitative findings reveal the dominance of semi-scientific reasoning due to limited conceptual integration. This study highlights that scientific literacy in psychiatric contexts is integrative, requiring the linkage between neurobiological mechanisms and behavioral interpretation, and underscores the importance of contextual and authentic biology learning.Keywords: Scientific literacy, maternal context, physiological changes, pregnancy complications, education, contextual learning